Carvedilol compared with Metoprolol succinate in the treatment and prognosis of patients with stable chronic heart failure - Fröhlich, Hanna; Zhao, Jingting Désirée; Täger, Tobias; Cebola, Rita; Schellberg, Dieter; Katus, Hugo; Frankenstein, Lutz (Circulation. Heart failure, 2015)
Background—β-Blockers exert a prognostic benefit in the treatment of chronic heart failure. Their pharmacological properties vary. The only substantial comparative trial to date—the Carvedilol or Metoprolol European Trial—has compared carvedilol with short-acting metoprolol tartrate at different dose equivalents. We therefore addressed the relative efficacy of equal doses of carvedilol and metoprolol succinate on survival in multicenter hospital outpatients with chronic heart failure.Methods and Results—Four thousand sixteen patients with stable systolic chronic heart failure who were using either carvedilol or metoprolol succinate were identified in the Norwegian Heart Failure Registry and The Heart Failure Registry of the University of Heidelberg, Germany. Patients were individually matched on both the dose equivalents and the respective propensity scores for β-blocker treatment. During a follow-up for 17 672 patient-years, it was found that 304 (27.2%) patients died in the carvedilol group and 1066 (36.8%) in the metoprolol group. In a univariable analysis of the general sample, metoprolol therapy was associated with higher mortality compared with carvedilol therapy (hazard ratio, 1.49; 95% confidence interval, 1.31-1.69; P<0.001). This difference was not seen after multivariable adjustment (hazard ratio, 0.93; 95% confidence interval, 0.57-1.50; P=0.75) and adjustment for propensity score and dose equivalents (hazard ratio, 1.06; 95% confidence interval, 0.94-1.20; P=0.36) or in the propensity and dose equivalent-matched sample (hazard ratio, 1.00; 95% confidence interval, 0.82-1.23; P=0.99). These results were essentially unchanged for all prespecified subgroups.Conclusions—In outpatients with chronic heart failure, no conclusive association between all-cause mortality and treatment with carvedilol or metoprolol succinate was observed after either multivariable adjustment or multilevel propensity score matching.
Gesehen am 14.07.2020